The stigma influence in the aids hearer acquaintance net - Silveira, Edilene AA; Carvalho, Ana MP (Brazilian Journal of Sexually Transmitted Diseases, 2006)
Introduction: aids carries a strong social stigma, which labels its bearer as unsuitable, immoral and socially unacceptable. Besides the bearer, theacquaintances of the Aids bearer may also suffer from stigma and rejection once they are seen as the bearer. Objective:the present work has as agoal identify how the stigma comes up in the speech of people who belong to the acquaintance net of the bearer and who frequent the general hospitalin the visit time. Methods:the data collection happened through interviews. Results:the contents derive from the dispositions acquired together withthe belonging social group during the long time, lived time and present time. The visitor, besides the contents of the historic time, is influenced by thelived time, i.e, by the previous living time with the ill person. This experience will make part of the visitor’s and visited person’s lived time. Conclu-sion:nowadays, despite the increased knowledge on Aids, the patient and his acquaitance net are still subject to isolation practices.